A study of demographic and psychographic factors on preference for travel activities among international and local tourists in Tanzania - Kara, Nasra Shokat (2017)
Tourism destination usually viewed as a combination of places that generates not just experience but offers a memorable destination experience to the tourists. The challenge for today's tourism destination agencies is for them to offer what is needed by travellers. Currently, the tourism sector in Tanzania is in stiff competition with countries such as Kenya and South Africa in attracting more tourists. For a country to stay ahead of the competition, it is imperative for tourism stakeholders to understand various means for attracting the tourists, including the preferences for travel activities. This study aimed at offering an integrated approach to understanding tourists' travel activities and assesses its relationship with travel motivation and personality traits. Responses from a total of 431 respondents aged 18 and above was obtained through convenience sampling and used in the analysis. The study identified visiting city attractions, islands and beaches as top three preferred travel activities by tourists and visiting casinos and nightclubs as the least preferred activities. Moreover, the study examined the differences in preference for travel activities among the domestic and international travel markets. It was found that the two markets significantly differ in terms of preferences for a beach, visiting city attractions, going to nightclubs, purchasing traditional clothes and jewellery, as well as camping. Additionally, the study also examined whether demographic factors such as marital status, family size and occupation have any significant effect on preference for travel activities. Of all demographic factors, only occupation was proven to have a significant influence on activities such as visiting beaches and islands and purchasing traditional clothes.